POTENTIAL OF SEA FLOW ENERGY AS A RENEWABLE ENERGY SOURCE (RENEWABLE ENERGY) ON THE CAPALULU HOLIDAY, NORTH MALUKU - Joni Widjayanto; Adi Bandono; I Made Jiwa Astika; Agung Tresnadi (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
One of the biggest obstacles to development progress in Eastern Indonesia is the unavailability of electricity,especially on small island islands. The potential of ocean currents is one of the most renewable sources ofenergy considering that the majority of Eastern Indonesia is the ocean and has not been utilized optimally. Thepurpose of writing this paper is to reference the calculation of ocean currents for Indonesian coastal islands thathave minimal electricity. This research method uses literature studies on the morphology of the flow velocity andwind that occurs in the Capalulu Strait and the calculation of the potential of electrical energy in the CapaluluStrait so that the results of this calculation are used as one of the renewable energy methods that are able tomeet the electricity needs of island islands. which has not been electrified in Indonesia, especially in the SulaIslands, North Maluku.Keywords: Electric Energy, Ocean Flow Turbine, Renewable Energy, Strait of Capalulu